Bilateral Multifocal Choroidal Osteoma with Choroidal Neovascularization - Mousavi MirNaghi; Shoeibi Nasser; Hosseini SeyedehMaryam; Saadat Targhi Ali (Case Reports in Ophthalmological Medicine)
Choroidal osteoma has been reported to be unilateral in approximately 80% of cases diagnosed with this condition. Herein we report the clinical characteristics and multimodal imaging findings in a rare case of bilateral multifocal choroidal osteoma. A 32-year-old female presented with decreased visual acuity (VA) in the right eye (20/100), though she had normal VA (20/20) in the left eye. Ophthalmoscopy and multimodal imaging investigation revealed bilateral multifocal choroidal osteoma complicated by choroidal neovascularization (CNV) in the right eye. Following three injections of intravitreal bevacizumab (IVB) for CNV in the right eye, VA improved to 20/40.